2021
DOI: 10.3390/medicina57050508
|View full text |Cite
|
Sign up to set email alerts
|

Post-Progression Survival Is Strongly Associated with Overall Survival in Patients Exhibiting Postoperative Relapse of Non-Small-Cell Lung Cancer Harboring Sensitizing EGFR Mutations

Abstract: Background and Objective: Patients with advanced non-small-cell lung cancer (NSCLC) harboring sensitizing epidermal growth factor receptor (EGFR) mutations show a good response to EGFR-tyrosine kinase inhibitors (EGFR-TKIs). The subsequent treatments influence the evaluability of the efficacy of front-line therapy on overall survival (OS). Consequently, we evaluated the associations of relapse-free survival (RFS) and post-progression survival (PPS) with OS in patients who exhibited postoperative relapse of EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Previous reports have suggested that OS correlates better with PPS than RFS in patients harboring EGFR ‐positive NSCLC who have undergone complete resection. 26 There is a report of significant disease‐free survival (DFS) prolongation with the administration of osimertinib as postoperative adjuvant chemotherapy in EGFR ‐mutated NSCLC. 27 However, if PPS is shown to alter OS in patients with postoperative recurrence, it is possible that DFS prolongation with adjuvant EGFR‐TKIs does not affect OS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that OS correlates better with PPS than RFS in patients harboring EGFR ‐positive NSCLC who have undergone complete resection. 26 There is a report of significant disease‐free survival (DFS) prolongation with the administration of osimertinib as postoperative adjuvant chemotherapy in EGFR ‐mutated NSCLC. 27 However, if PPS is shown to alter OS in patients with postoperative recurrence, it is possible that DFS prolongation with adjuvant EGFR‐TKIs does not affect OS.…”
Section: Discussionmentioning
confidence: 99%